Function of Metallothionein-3 in Neuronal Cells: Do Metal Ions Alter Expression Levels of MT3? - Bousleiman, Jamie (Int J Mol Sci, 2017)
A study of factors proposed to affect metallothionein-3 (MT3) function was carried out to elucidate the opaque role MT3 plays in human metalloneurochemistry. Gene expression of Mt2 and Mt3 was examined in tissues extracted from the dentate gyrus of mouse brains and in human neuronal cell cultures. The whole-genome gene expression analysis identified significant variations in the mRNA levels of genes associated with zinc homeostasis, including Mt2 and Mt3. Mt3 was found to be the most differentially expressed gene in the identified groups, pointing to the existence of a factor, not yet identified, that differentially controls Mt3 expression. To examine the expression of the human metallothioneins in neurons, mRNA levels of MT3 and MT2 were compared in BE(2)C and SH-SY5Y cell cultures treated with lead, zinc, cobalt, and lithium. MT2 was highly upregulated by Zn(2+) in both cell cultures, while MT3 was not affected, and no other metal had an effect on either MT2 or MT3.